Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Virgin Coconut Oil (VCO) Di Jempong Baru Kecamatan Sekarbela Kota Mataram Nusa Tenggara Barat - Mina Ainta Putri; Eka Cahyani; Firman Ali Rahman; R. Didi Kuswara; Alfian Pujian Hadi (Aksi: Jurnal Pengabdian Masyarakat, 2024)
Virgin Coconut Oil (VCO) is a processed product originally from Indonesia made from fresh coconut meat which is processed at low temperatures or without heating, so that the important contents of the oil can still be maintained. This training activity aims to provide knowledge and skills to the people of East Jempon, Sekarbela District, Mataram City, about making Virgin Coconut Oil (VCO) as an effort to improve economic welfare. The training was carried out through seminars and direct practice involving participants in the natural VCO production process without heating. The results of the training showed that the community was able to understand the technique of processing coconut into VCO and its health benefits. In addition, this training provides opportunities for the community to develop small businesses based on VCO products. Making VCO naturally produces high-quality products, is not rancid, and has a long shelf life. Thus, this training has succeeded in improving the skills and knowledge of the community in processing coconut into products of high economic value.